Legal Protection of Women as Victims of Trafficking under the Provisions of Law No. 12 of 2017 - Kurniati Siregar (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Asean Convention Against Trafficking In Persons, Especially Women and Children is a convention that has been ratified in Indonesia into Law Number 12 of 2017 containing opposition to trafficking in persons, especially women and children and an important role and duties of the state in order to fight against trafficking in persons.The protection of women as a victim of trafficking in persons is contained in Article 14 which contains 14 points of tasks that must be carried out by the state in protecting victims of trafficking in persons. Prevention of trafficking in persons that must be carried out by the state is contained in Article 11 which contains 5 points of preventive measures.The fact that happened in Indonesia, this regulation has not been realized and the benefits have not been felt by the peoples especially women who have been involved and being victims of trafficking in persons. New regulations that are in line with international law and protect the vistims have not been made as a follow-up to this convention, and implementation and monitoring are still at a low level